2021
DOI: 10.1136/bmjopen-2021-049339
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of implementation outcome research: a scoping review protocol

Abstract: IntroductionA 2011 paper proposed a working taxonomy of implementation outcomes, their conceptual distinctions and a two-pronged research agenda on their role in implementation success. Since then, over 1100 papers citing the manuscript have been published. Our goal is to compare the field’s progress to the originally proposed research agenda, and outline recommendations for the next 10 years. To accomplish this, we are conducting the proposed scoping review.Methods and analysisOur approach is informed by Arks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Second, this paper was not an abstract theoretical exercise. The development of the proposed recommendations—and the realization of the need to do so—was directly informed by our hands-on experience conducting a scoping review [ 25 ]. Third, our recommendations can be used to elaborate upon outcomes-related sections of existing guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, this paper was not an abstract theoretical exercise. The development of the proposed recommendations—and the realization of the need to do so—was directly informed by our hands-on experience conducting a scoping review [ 25 ]. Third, our recommendations can be used to elaborate upon outcomes-related sections of existing guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a scoping review aimed at describing how the field conceptualized, measured, and advanced theory around implementation outcomes since 2011 [ 25 ], we identified 358 empirical studies published in peer-reviewed journals that cited the original paper and assessed one or more implementation outcomes. We found that while anchored by the conceptual definitions from the 2011 taxonomy, these studies varied substantially in how implementation outcomes were reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Exploration, Preparation, Implementation, and Sustainment framework emphasizes sustainability integrated as a critical part of implementation. 17 Additionally, sustainability, defined as “the extent to which a newly implemented treatment is maintained or institutionalized within a service setting’s ongoing, stable operations,” 18 is often an implementation outcome that strategies are evaluated against.…”
Section: Building Health System Resilience By Increasing Affordabilit...mentioning
confidence: 99%
“…As defined by Proctor et al, 43 implementation outcomes are “the effects of deliberate and purposive actions to implement new treatments, practices, and services.” In addition to the aforementioned RE-AIM model, other implementation outcomes include acceptability, adoption, appropriateness, costs, feasibility, fidelity, penetration (or reach), and sustainability. 44,45 Options for measuring these outcomes include, for instance, (a) conducting focus groups with practitioners to determine the extent to which an intervention can be sustainably used in practice, (b) completing chart reviews to evaluate practitioners’ adoption of a particular intervention or standardized assessment, and (c) observing the behavioral patterns of practitioners to assess their level of fidelity to an intervention protocol. Proctor et al 43 provide in-depth descriptions of each of these implementation outcomes as well as recommendations for measurement.…”
Section: Introductionmentioning
confidence: 99%